KARAKTERISTIK REMAJA DENGAN RIWAYAT GIZI BURUK DAN PENDEK PADA USIA DINI - Arnelia Arnelia (Jurnal Gizi dan Pangan, 2011)
Severe malnutrition and linear growth retardation during early childhood were prevalent in developing countries. Objectives of this study was to study adolescent characteristics with the severe malnutrition and linear growth disorder history in early age. A followed-up study were caried out among 93 adolescents aged 10-17 years in Bogor. Subjects admitted to Nutrition Clinic Bogor at the age of below three years, suffered from severe malnutrition as well as stunted at first enrollment. Data collected including weight and height, socio economic status, parent’s weight and height, subject’s characteristicts and secondary data at first enrollment to the clinic from medical records including weight, height, diagnozed, parent’s characteristics. As many as 36.6% subjects were categorized as normal base on height for age (HFA), higher among males (45.3%) than females (32.3%). Higher proportion of normal HFA adolescent were found on farmer or driver father, house keeper mother and mother with junior high school education background. There was no relationship between aged at first enrollment to nutrition clinic as well as puberty status with HFA during adolescent. As many as 52% of adolescents achieve normal HFA whose mother’s height > 150 cm, in the opposite 73.8% of stunted teenage with mother’s height <150 cm. There is a linkage achieving linear growth among adolescent experienced severe malnutrition and linear growth disorders during early childhood with parental employment, maternal education and maternal height.